Resveratrol Reduce the Severity of Anemia and Thrombocytopenia in Plasmodium berghei ANKA-Infected Mice - Faizal Hermanto; Aqila Refiani; Fahmi Ahsanul Haq (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Malaria is an infectious disease with a high mortality rate. One of the complications of malaria is blood disorders. Hematological disorders such as anemia and thrombocytopenia are common in malaria infection. Resveratrol has been reported to have antimalarial activity. Objective: This study aimed to evaluate the effect of resveratrol in reducing the severity of anemia and thrombocytopenia in Plasmodum berghei-infected mice. Methods: The study began with parasite inoculation in mice. After the mice were infected, and randomly grouped into negative control, chloroquine 20 mg/kg (positive control), and resveratrol with doses 25, 50, and 100 mg/kg. The mice's blood profile was measured on day 0 and day 4 using a hematology analyzer. Results: The results showed that after administration of resveratrol at various doses, the number of RBC, hemoglobin, hematocrit and platelets was higher than the control. Conclusion: It can be concluded that resveratrol can reduce the severity of anemia and thrombocytopenia in mice infected with P. berghei.